2016
DOI: 10.1016/j.jpag.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Increased Body Mass Index Associated with Increased Risky Sexual Behaviors

Abstract: Study Objective The increasing prevalence of adolescent obesity has led to consideration of the potential effect of obesity on risky sexual behaviors. The current study examined whether body mass index (BMI) was related to age at sexual debut, type of sexual behavior, partner number, and condom use in a population of adolescent women at high risk for obesity and risky sexual behaviors. Study Design Cross-sectional examination of 860 sexually active, predominantly minority, adolescent women who received medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…The adolescents with early coitarche could have extreme sexual activities such as anal sex and oral sex, which can affect to sexually transmitted diseases (STD). Anal sex without a barrier can increase the risk of HIV five until twenty times compared to vaginal sex [23]. On another side, Nigeria Demographic and Health Survey suggests a considerably strong relationship between early sexual debut and a lifetime experience of having multiple sexual partners, which can increase STD too [16].…”
Section: Discussionmentioning
confidence: 99%
“…The adolescents with early coitarche could have extreme sexual activities such as anal sex and oral sex, which can affect to sexually transmitted diseases (STD). Anal sex without a barrier can increase the risk of HIV five until twenty times compared to vaginal sex [23]. On another side, Nigeria Demographic and Health Survey suggests a considerably strong relationship between early sexual debut and a lifetime experience of having multiple sexual partners, which can increase STD too [16].…”
Section: Discussionmentioning
confidence: 99%
“…(10,20) On the other hand, other authors found an association between high BMI and risky sexual behaviors, such as not using condoms and consumption of alcohol or drugs before their last intercourse. (2,7-9)…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found an association between high BMI and risky sexual behaviors, such as not using condoms and consuming alcohol or other drugs before the last intercourse. (2,7-9) In addition, weight misperception has also been identified as an important factor associated with risky behaviors. (10)…”
Section: Introductionmentioning
confidence: 99%
“…Over a lifetime, acute infections represent the most frequent sources of short-term functional limitation among all age groups, with asthma and short-term injuries increasing in later childhood, and obesity and depression occurring at higher rates as children move into adolescence (Gordon et al, 2016). In adolescents and young adults, substance abuse emerges as a more common near-and longer-term health threat (Blum and Qureshi, 2011), as does risky sexual behavior and violence in some populations.…”
Section: Health and Disease Over The Life Coursementioning
confidence: 99%